Al-’Alâqah Bayna Hifdzhi al-Qurân wa Mahârati al-Qirâah al-Jahriyyah li Thullâbi Ma’had al-Mu’allimîn li Jam’iyyati Muhammadiyyah Bukit Tinggi - Nurlaila; Yossi Isnaini Juli Astika; Kamaluddin (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2022)
The purpose of this study was to determine the relationship between memorizing the Qur’an and the ability to read aloud Arabic at the Mu’alimin Islamic Boarding School Muhammadiyah Sawah Dangka Bukittinggi. The research sample amounted to 66 students obtained through a systematic sampling technique. The data collection technique used in this paper was a test consisting of a memorizing of the Qur’an and a test of reading aloud Arabic. The data analysis technique used is the Pearson product-moment correlation analysis technique. The results showed that ro was greater than rt (0.424 > 0.242) at a significance level of 5%, therefore the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. The conclusion is that there is a significant relationship between the memorization of the Qur’an and the ability to read Arabic aloud and the level of the relationship is in the medium category.